(untitled) (Research, Society and Development, 2020)
The objective of this work is to propose a methodology for teaching physics, exploring the multiple intelligences, being them; linguistic, logical mathematical and visuospatial. The analysis and data collection were carried out at the Francisco Sá Sobrinho municipal public school, where classes were held, located in the city of São João dos Patos Maranhão in the ninth year of elementary school, the choice this year is due to the fact that students have their first contact with the specifications of the physics discipline. The methodology used was bibliographic research and then a field research with pedagogical interventions and differentiated classes, which made it possible to obtain information about how the difficulties of students in the physics discipline occur in situations of stimulating linguistic, mathematical and visuospatial intelligences . The data obtained received a quantitative and qualitative treatment. With the pedagogical interventions, the students showed good results, expressed more interest, liked the classes, and during the same they could feel free to express themselves, question, show their points of view, moreover, in the evaluative activities the students did not they get the same weight as an assessment, where they usually get nervous. Thus, the research intends to use Gardner’s Multiple Intelligences for teaching and learning in the discipline of Physics.